Medical students' perceptions of general practice as a career; a phenomenological study using socialisation theory. Issue 4 (4th July 2018) - Reid, Katherine; Alberti, Hugh
ABSTRACT: The ageing population and push to community care has significantly increased the workload of General Practitioners (GPs) in the UK and internationally. In an attempt to tackle this, NHS England has promised 5000 more GPs by 2020/21; however, recruitment is in crisis with GP training posts remaining unfilled. Little research has been carried out to assess the fundamental questions of what medical students' perceptions of General Practice are and what shapes their perceptions at medical school. We aimed to explore medical students' conceptualisations of being a GP and specifically the role of the medical school in shaping their perceptions. Two focus groups of year one and year four medical students were undertaken using an interpretive phenomenological approach. Our study has revealed that medical students perceive General Practice to lack prestige and challenge. These perceptions come, at least in part, from a process of socialisation within medical school, whereby medical students internalise and adopt their role models' perceptions and values, and the values portrayed by the hidden curriculum in their medical school culture. Perceived external pressures to pursue a career in General Practice can have a negative influence and medical schools should be made aware of this.